The Role of Utilitarian Value, Hedonic Value, and Emotional Value on Purchase Intention through Shopee Live - Siti Wardah Pratidina Nasution; Siti Ummi Arfah Nasution (Sultan Publisher, 2023)
This research aims to analyze the role of utilitarian value, hedonic value, and emotional value on purchase intention of Somethinc’s products through Shopee Live. A quantitative approach was used through distributing questionnaires and a sample of 82 respondents was obtained. The validity test using loading factors and Average Variance Extracted (AVE) shows valid values. The reliability test using composite reliability values had met the criteria. The data analysis technique used is SEM-PLS (Partial Least Squares). The hypothesis was tested with SmartPLS 3.0, showing that utilitarian value had a positive and significant effect on purchase intention with a significance value of 0.032, hedonic value had a positive and insignificant effect with a value of 0.066 on purchase intention, and emotional value had a positive and significant effect on purchase intention with a value of 0.001. The influence of utilitarian value, hedonic value and emotional value variables on purchase intention is 65% with an R-square value of 0.648, while 35% is explained by other variables outside this research.